DE VOLGORDE VAN DE VOLKENPROFETIEËN IN HET BOEK JEREMIA - Peels, H GL (Acta Theologica, 2018)
THE ORDER OF THE ORACLES AGAINST THE NATIONS IN THE BOOK OF JEREMIAH The textual tradition of the Book of Jeremiah shows two different orders of the collection of the Oracles Against the Nations (OAN). Recently, an increasing majority of scholars have given preference to the sequence of the OAN collection in JerLXX as being the more original one. It remains uncertain, however, whether this growing consensus is, in fact, valid. In this article, I develop four arguments that question the preference for the Greek order of the OAN collection in Jeremiah. Alternatively, I present a hypothesis for the originality of the MT order and a possible reason for its reworking at a later period.